Comparative Analysis of Corporate Social Responsibility Islamic Banking in Indonesia and Malaysia - Anggita Nurcahyani; Anis Suriati Binti Ahmad (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2021)
In Islamic Banking, the process of carrying out the operating system must pay attention to the values of Islamic teaching. As an Islamic financial institution, Islamic banking should be beneficial for humans and the environment. The role of its banking can be applied through Corporate Social Responsibility (CSR). Indonesia and Malaysia are countries that already have an Islamic bank. The goal of this research is to compare the differences between Islamic banking CSR in Indonesia and Malaysia. The method used in this research is a quantitative method using secondary data from the annual financial statements of Islamic banks in Indonesia and Malaysia within three years. This research uses the ISR Index (Islamic Social Reporting), which consists of 6 categories. Then, this research also uses Content Analysis to find out CSR disclosures and Mann Whitney U Test to find out CSR differences from each bank. The results from this research are Islamic banking in Indonesia gets the highest score in all categories than Islamic banking in Malaysia. But, no one of both countries which disclosure 100% CSR items.